2021
DOI: 10.1101/2021.03.16.435577
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loss of glutamate transportereaat2aleads to aberrant neuronal excitability, recurrent epileptic seizures and hypoactivity

Abstract: Astroglial excitatory amino acid transporter 2 (EAAT2, GLT-1, SLC1A2) regulates the duration and extent of neuronal excitation by removing glutamate from the synaptic cleft. Human patients with altered EAAT2 function exhibit epileptic seizures, suggesting an important role for astroglial glutamate transporters in balancing neuronal excitability. To study the impact of EAAT2 function at the neural network levels, we generated eaat2a mutant zebrafish. We observed that eaat2a-/- mutant zebrafish larvae display re… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 91 publications
0
5
0
Order By: Relevance
“…Both head-and tail-stimulated slc1a2b tk57/tk57 embryos reach the maximum rostral-caudal angle later in the response than wild-type embryos, which could explain why no touch location differences were found for the maximum angle of slc1a2b tk57/tk57 responses. Although slc1a2b is not expressed in the Mauthner cell, slc1a2bexpressing glial cells surround the Mauthner array at 48 hpf (Hotz et al, 2022;McKeown et al, 2012). Based on the data presented here, we propose that the disrupted kinematic profile of slc1a2b tk57/tk57 embryos may be due to a reactivation of escape circuitry late into the response.…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations
“…Both head-and tail-stimulated slc1a2b tk57/tk57 embryos reach the maximum rostral-caudal angle later in the response than wild-type embryos, which could explain why no touch location differences were found for the maximum angle of slc1a2b tk57/tk57 responses. Although slc1a2b is not expressed in the Mauthner cell, slc1a2bexpressing glial cells surround the Mauthner array at 48 hpf (Hotz et al, 2022;McKeown et al, 2012). Based on the data presented here, we propose that the disrupted kinematic profile of slc1a2b tk57/tk57 embryos may be due to a reactivation of escape circuitry late into the response.…”
Section: Discussionmentioning
confidence: 57%
“…Interestingly, slc1a2b mutants harboring nonsense mutations are able to swim spontaneously at 5 dpf (Hotz et al, 2022), whereas the slc1a2b tk57/tk57 allele described here and in McKeown et al, 2012 is fully paralyzed by 96 hpf. This difference could be explained by the nature of the mutations; premature termination codons generated using CRISPR-Cas9 have been shown to trigger genetic compensation via transcriptional adaptation (El-Brolosy et al, 2019;Sztal & Stainier, 2020).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Although hyperlocomotor activity is a surrogate readout of seizure-like behaviour in zebrafish (validated usually with LFP recordings) (Afrikanova et al, 2013;Baraban, Dinday and Hortopan, 2013), a recent study found that larvae with seizure-like discharges were hypoactive in the locomotor test (Hotz et al, 2021). Suggesting that the type of seizures may inform the behavioural readout i.e.…”
mentioning
confidence: 99%